تأثير مصدر الرواسب النهرية في بعض خصائص الترب الرسوبية المحاذية لنهر شط العرب - كاظم محمد أحمد (University of Thi-Qar Journal of Science, 2013)
The study was conducted to know the effect of sediments fluvial source on some alluvial soilsproperties abutting for Shatt Alarab River. Two strips were chosen the first stripe at Alharitha region which represented by pedons 1 and 2, while the second stripe at Al seeba region which represented by pedons 3 and 4. The sedimentation sources were Shatt Alarab at the first stripe while the sedimentation sources were Karun River and Shatt Alarab at the second stripe. The result of investigated soils showed varies in some morphology properties according to landscape position and the different sedimentation sources (river). There are variations in the soil color values through the Hue which was at the first stripe 10 YR while at the second stripe was 7.5 YR and different Value and Chroma between the two stripes.Also, the dominance structure was angular blocky and this showed effect of sedimentation type and its source and sedimentation process conditions. The results of physical analysis showed sudden variation of texture has been found in both vertical and horizontal direction with dominance of clay and silt particles and decreasing in sand particle percent except the pedon 1 and 3 with horizons moderate fine texture and horizons moderate . And that dependes on sedimentation rate according to distance from the sedimentation sources (river).